Vitamin E and athletic performance - Telford, R. D. (Asia Pacific Journal of Clinical Nutrition, 1993)
Vitamin E has been of interest to sports people for many years, with reports of its dietary supplementation in the 1950s. In the last decade there has been a resurgence in the interest in the relationship between vitamin E and athletic performance and animal studies have demonstrated that endurance is reduced in vitamin E deficiency. Much of the recent research has centred around the antioxidant properties of vitamin E and it seems that these properties are in part responsible for the improvement of aerobic power of humans at medium to high altitude venues following supplementation of the vitamin. However, there have been no similar reports relating to sea-level performance. On the other hand, one recent study has indicated that supplementation of vitamin E to athletes consuming the recommended daily intake (RDI) elicited a reduction in indicators of muscle damage following an exercise bout. Furthermore, vitamin E is implicated in maintenance of both optimal immune function and optimal blood viscosity, both factors being important in athletes' ability to train and compete, but it remains to be seen whether supplementation over the RDI has any beneficial effects. So, there seems 'little doubt that vitamin E deficiency will impair athletic performance and there is also some evidence that supplementation of vitamin E on top of the RDI may provide some advantage for the intensely training athlete, especially those training at altitude.